ANALISIS PEMBEBANAN STATIK PADA RANGKA BOGIE AUTOMATIC PEOPLE MOVER SYSTEM (APMS)MENGGUNAKAN STANDAR UIC-615 DENGAN FINITE ELEMENT - Utomo, Setyo Margo (Majalah Ilmiah Pengkajian Industri, 2017)
Bogie is a unity that supports the construction of railway facilities monorail when running on the track. Bogie frame is a construction to support the carbody against imposition. The purpose of this analysis is to determine and ascertain the limits static strength numerical order before the prototype bogie frame through static testing or verification stage design. Stages in this research is the collection of data and bogie drawing APMS of PT.INKA Madiun, and then to identify the 3D CAD model of the structure of the bogie frame, then conducted to determine the boundary conditions for the imposition of simulated static load.Base on standard UIC-615 there are only two types of load that is vertical and transversal, the maximum value is 53 234 and 48 619 N. Result of static testing for static tests with exceptional load, the greatest deformation of 0.5 mm occurs on the balanced wheel, and a maximum stress of 175,97 MPa which lies in the foundation of anti-roll bar, due to transverse load occurring on the pedestal of the anti-roll bar is quite large. Safety factor value that occurs in the area of anti-roll bar is quite low, 1,39.The simulation results for the static testing workload (Static test to Simulate the main in-service load) obtained value of the lowest safety factor of 2.39 with a maximum stress value of 102.26 MPa and deformation of 0,339 mm at the time of load case 8.